2019
DOI: 10.1021/acs.iecr.9b03970
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Electrochemical Reduction of CO2 to Formic Acid/Formate: Effect of pH on the Downstream Separation Process and Economics

Abstract: We use a high-pressure semicontinuous batch electrochemical reactor with a tin-based cathode to demonstrate that it is possible to efficiently convert CO 2 to formic acid (FA) in low-pH (i.e., pH < pK a ) electrolyte solutions. The effects of CO 2 pressure (up to 50 bar), bipolar membranes, and electrolyte (K 2 SO 4 ) concentration on the current density (CD) and the Faraday efficiency (FE) of formic acid were investigated. The highest FE (∼80%) of FA was achieved at a pressure of around 50 bar at a cell poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 131 publications
0
118
0
Order By: Relevance
“…In a CO 2 electrolyser for methanol production, when the produced CO 2 remains dissolved due to an applied pressure, the avoided typical gas regeneration step and CO(g) compression step save more than 150 kJ mol −1 CO 2 [46]. High pressure electrolyser (up to 40 bar) is also reported to increase the current efficiency of CO 2 reduction to formic acid/formate [351,352]. Moreover, a high pressure CO 2 (g) is required for the transportation in the pipes, enhanced oil recovery or geological CO 2 sequestration for underground injection.…”
Section: Co 2 Utilizationmentioning
confidence: 99%
“…In a CO 2 electrolyser for methanol production, when the produced CO 2 remains dissolved due to an applied pressure, the avoided typical gas regeneration step and CO(g) compression step save more than 150 kJ mol −1 CO 2 [46]. High pressure electrolyser (up to 40 bar) is also reported to increase the current efficiency of CO 2 reduction to formic acid/formate [351,352]. Moreover, a high pressure CO 2 (g) is required for the transportation in the pipes, enhanced oil recovery or geological CO 2 sequestration for underground injection.…”
Section: Co 2 Utilizationmentioning
confidence: 99%
“…on the CO 2 reduction reaction (CO2RR) . The current status of the CO2RR is that only small molecules like carbon monoxide (CO), formate (HCOO − ) and ethylene (C 2 H 4 ) can be obtained with high Faradaic efficiencies (FEs) and current densities (CDs). It is also clear that the CO2RR in the liquid phase is intrinsically limited by mass transfer and one has to rely on gas diffusion electrodes (GDEs) to achieve industrially relevant reaction rates (i. e., CDs >100 mA/cm 2 ) …”
Section: Figurementioning
confidence: 99%
“…Indeed, according to several authors, the pressure can affect the selectivity between CO 2 and water reduction, the distribution of the CO 2 reduction products and overpotentials need to drive the reaction [37][38][39][40][41][42][43][44][45][46]. In particular, a dramatic effect of pressure on electrochemical conversion of CO 2 to formic acid in aqueous electrolyte at tin cathodes was observed by some authors [42,44,[56][57][58]. Moreover, among the limited number of studies employing high pressure for the CO 2 reduction, Pardal et al [54] have showed that the combination of high CO 2 pressure with ionic liquidbased electrolyte, as CO 2 adsorption media, can significantly improve the productivity of the process by maintaining high selectivity of the process towards CO (CO productivity of about 0.25 mmol cm −2 coupled with a CE CO ~ 97% after a passed charge of about 50 °C at 30 bar, 45 °C and − 0.8 V vs RHE).…”
Section: Introductionmentioning
confidence: 98%